ANALISIS SENYAWA KIMIA DALAM EKSTRAK KLOROFOM BUNGA KAMBOJA (Plumeria alba) DENGAN GC-MS - Santi Nur Handayani; Kapti Riyani (Molekul, 2008)
lumeria alba is called frangipani is one of Apocynaceae family’s plant. Frangipani is potentially used as traditional medicine, for example as an antiinflamation drugs. It has not been yet done an extensive reasearch on the chemical compound content of frangipani. The reasearch was conducted to investigate some chemical constituents by using Gas Chromatography-Mass Spectrometer (GC-MS). Extraction of chemical compound of frangipani has been conducted by soxhletasi using n-hexane as solvent followed by chloroform and ethyl acetate. Then chloroform extract was identified by GC-MS. The result showed that extract of chloroform contained : palmitic acid, clionasterol, fucosterol, fagarasterol and methyl commate B respectively.